A single-blinded, randomized, controlled trial comparing efficacy between low-fluence alexandrite 755-nm picosecond laser and low-fluence neodymium-doped yttrium aluminum garnet (Nd:YAG) 1064-nm picosecond laser for the treatment of ultraviolet B-induced hyperpigmentation - Vachiramon V. (2023)
Background: Hyperpigmentation is a common concern of patients in dermatology clinics. Although there are many treatment options, lasers are considered a promising therapy for various hyperpigmentary conditions. Objectives: This study aims to evaluate the efficacy of alexandrite 755-nm picosecond and neodymium-doped yttrium aluminum garnet (Nd:YAG) 1064-nm picosecond lasers for the treatment of ultraviolet B (UVB)-induced hyperpigmentation in Asians. Materials and Methods: A randomized, single-blinded study was conducted. UVB-induced hyperpigmentation was performed in three spots by narrowband UVB. After 2 weeks, these three spots were allocated into 755-treated, 1064-treated, and control sites. Patients received weekly laser treatments for five sessions. Follow-ups were scheduled at 1 and 2 months after the last session. Results: Twenty patients attended the study. Overall, 755-nm and 1064-nm picosecond lasers showed a significant improvement in the mean lightness index (L*) compared to the control site, which started at Day 49 and Day 77, respectively. The mean L* of the 755-nm-treated site was also higher than that of the 1064-nm–treated site at Day 105 (p ≤ 0.001). Initially, the mean L*, physician's visual analog scale (VAS), and patient satisfaction with the 1064-nm picosecond laser were better than those with the 755-nm picosecond laser. Nevertheless, an inversion of the mean L* and VAS was noted at Day 49, whereas the mean patient satisfaction was noted at Day 77. In the subgroup analysis, a 755-nm picosecond laser effectively treated Fitzpatrick skin types (FPTs) III and IV. However, the mean L* of the 1064-nm picosecond laser was not significantly different from that of the control for FPT4. Conclusion: The alexandrite 755-nm picosecond and Nd:YAG 1064-nm picosecond lasers appear to be effective and safe modalities for treating UVB-induced hyperpigmentation. With the setting employed in this study, the outcome after the 755-nm picosecond laser treatment seemed superior to that of the 1064-nm picosecond laser treatment, especially for FPT4.